1.04k likes | 1.19k Views
Technically Speaking: Have Your Cake And Eat It Too!. Steven Rudich Andrew’s Leap 2011. Anne Willan’s Look & Cook books are the model of technical exposition. Presumes little . Each recipe is self contained Picture of each ingredient Picture of each tool Picture of each step
E N D
Technically Speaking:Have Your Cake And Eat It Too! Steven RudichAndrew’s Leap 2011
Anne Willan’s Look & Cook books are the model of technical exposition.
Presumes little. • Each recipe is self contained • Picture of each ingredient • Picture of each tool • Picture of each step • Picture of techniques • A kid can do it!
Promises much. • Professional recipes • Professional techniques • Cooking school curriculum
Optimized content. “All the great recopies and techniques were collected and evaluated. Experts masterfully distilled the material, without tossing out any key idea or recipe.”
Substantial promise. “From thousands, the 40 key recipes and techniques of • French Country Cooking”.
Have your cake, and eat it too! • Presumes little. • Promises much. • Step by step illustrations anticipate every problem. • Provokes active curiosity .
Technical Speaking • Presume the least. • Promise the most. • Pamper their brains. • Provoke active curiosity
Talk Outline(Standard practice) • Title: Standard Security Protocols • SSL • RSA • DES • DSS • MACs The SSL protocol was first developed by the Netscape corporation and then extended to TLS ………….
Title: Standard Security Protocols • SSL • RSA • DES • DSS • MACs Presumes Jargon Content promise unclear Causes emotional anxiety Curiosity impulse is squandered
Title: Standard Security Protocols • “SSL” • “RSA” • “DES” • “DSS” • “MACs” Internet Security is an ocean of confusing acronyms. What do these stand for exactly? How do they work? Why are they important technically and economically? By the end of today’s lecture you should be able to answer these questions.
Pamper their brains. Brains are perceptually, computationally, and emotionally constrained.
Intellectual Fantasy:Brain To Brain Transfer More! Harder!Faster!
Platonic Fantasy:A Talk Is An Aesthetic Object Perfect Truth Is Beauty.
Human Reality When’s lunch? blah, blah, blah What’s a DAG?
Demands Accumulate,Brains Deplete! • Visual Processing.
Demands Accumulate,Brains Deplete! • Visual Processing. • Auditory Processing.
Demands Accumulate, Brains Deplete! • Visual Processing. • Auditory Processing. • Concentration.
Demands Accumulate,Brains Deplete! • Visual Processing. • Auditory Processing. • Concentration. • Calculation.
Demands Accumulate,Brains Deplete! • Visual Processing. • Auditory Processing. • Concentration. • Calculation. • Short Term Memory.
Demands Accumulate,Brains Deplete! • Visual Processing. • Auditory Processing. • Concentration. • Calculation. • Short Term Memory. • Recall From Long Term Memory.
Demands Accumulate, Brains Deplete! • Visual Processing. • Auditory Processing. • Concentration. • Calculation. • Short Term Memory. • Recall From Long Term Memory. • Stress Of Unresolved Concerns.
Demands Accumulate,Brains Deplete! • Visual Processing. • Auditory Processing. • Concentration. • Calculation. • Short Term Memory. • Recall From Long Term Memory. • Stress Of Unresolved Concerns. • Etc . . . Duh.
Work Hard To Be Easy! • Be easy to see • Minimize info/slide • .
Work Hard To Be Easy! • Be easy to hear • Speak up, or use mic • Enunciation habits matter
Work Hard To Be Easy! • Memory and reference • Eliminate pronouns • (its, this, that) • unless you are pointing
a b b a a a b a b b Work Hard To Be Easy! • Kid Friendly Illustrations.
Pamper their brains! Brain stress is additive.
Correspondence is content! Spell out the exact correspondencebetween arguments in different representations.
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 2S = n(n+1) S = ½n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 2S = n(n+1) S = ½n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 2S = n(n+1) S = ½n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 2S = n(n+1) S = ½n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 2S = n(n+1) S = ½n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 s = 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 1 2 n 2S = n(n+1) S = ½n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof s = S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 s = 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 1 2 n 2S = n(n+1) S = ½n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof s = S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 s = 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 1 2 n 2S = n(n+1) 2s = S = ½n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof s = S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 s = 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 1 2 n 2S = n(n+1) 2s = S = ½n(n+1) n+1 = n(n+1)
1 + 2 + 3 + … + n-1 + n = ½n(n+1) Algebraic Proof Geometric Proof s = S = 1 + 2 + 3 + + n-1 + n S = n + n-1 + n-2 + … + 2 + 1 s = 2S = n+1 + n+1 + n+1 + … + n+1 + n+1 1 2 n 2S = n(n+1) 2s = S = ½n(n+1) n+1 S = ½n(n+1)
I own 3 beanies and 2 ties. How many different ways can I dress up in a beanie and a tie?
t2 b1 t1 b2 b2 t2 b3 b3 b1 t1 t2 t1 b3 b1 b2 t t2 t t2 t2 t
b3 b b2 b b2 b3 t2 t t t2 t2 t b2t b3t b3t2 bt2 b2t2 bt ( b + b2 + b3 )( t + t2 )=
b3 b b2 b b2 b3 t2 t t t2 t2 t b2t b3t b3t2 bt2 b2t2 bt ( b + b2 + b3 )( t + t2 )= bt +
b3 b b2 b b2 b3 t2 t t t2 t2 t b2t b3t b3t2 bt2 b2t2 bt ( b + b2 + b3 )( t + t2 )= bt + bt2 +
b3 b b2 b b2 b3 t2 t t t2 t2 t b2t b3t b3t2 bt2 b2t2 bt ( b + b2 + b3 )( t + t2 )= bt + bt2 + b2t +
b3 b b2 b b2 b3 t2 t t t2 t2 t b2t b3t b3t2 bt2 b2t2 bt ( b + b2 + b3 )( t + t2 )= bt + bt2 + b2t + b2t2 +
b3 b b2 b b2 b3 t2 t t t2 t2 t b2t b3t b3t2 bt2 b2t2 bt ( b + b2 + b3 )( t + t2 )= bt + bt2 + b2t + b2t2 + b3t +
b3 b b2 b b2 b3 t2 t t t2 t2 t b2t b3t b3t2 bt2 b2t2 bt ( b + b2 + b3 )( t + t2 )= bt + bt2 + b2t + b2t2 + b3t + b3t2